Influence of Cavitation on Unsteady Vortical Flows in a Side Channel Pump - Yefang Wang; Fan Zhang; Shouqi Yuan; Ke Chen; Feng Hong; Desmond Appiah (Chinese Journal of Mechanical Engineering, 2023)
Abstract Previous investigation on side channel pump mainly concentrates on parameter optimization and internal unsteady vortical flows. However, cavitation is prone to occur in a side channel pump, which is a challenging issue in promoting performance. In the present study, the cavitating flow is investigated numerically by the turbulence model of SAS combined with the Zwart cavitation model. The vapors inside the side channel pump firstly occur in the impeller passage near the inlet and then spread gradually to the downstream passages with the decrease of NPSHa. Moreover, a strong adverse pressure gradient is presented at the end of the cavity closure region, which leads to cavity shedding from the wall. The small scaled vortices in each passage reduce significantly and gather into larger vortices due to the cavitation. Comparing the three terms of vorticity transport equation with the vapor volume fraction and vorticity distributions, it is found that the stretching term is dominant and responsible for the vorticity production and evolution in cavitating flows. In addition, the magnitudes of the stretching term decrease once the cavitation occurs, while the values of dilatation are high in the cavity region and increase with the decreasing NPSHa. Even though the magnitude of the baroclinic torque term is smaller than vortex stretching and dilatation terms, it is important for the vorticity production along the cavity surface and near the cavity closure region. The pressure fluctuations in the impeller and side channel tend to be stronger due to the cavitation. The primary frequency of monitor points in the impeller is 24.94 Hz and in the side channel is 598.05 Hz. They are quite corresponding to the shaft frequency of 25 Hz (f shaft = 1/n = 25 Hz) and the blade frequency of 600 Hz (f blade = Z/n =600 Hz) respectively. This study complements the investigation on cavitation in the side channel pump, which could provide the theoretical foundation for further optimization of performance.